Monovalent XBB.1.5 COVID-19 vaccine effectiveness against hospitalisations and deaths during the Omicron BA.2.86/JN.1 period among older adults in seven European countries: A VEBIS-EHR network study - Baltazar Nunes; James Humphreys; Nathalie Nicolay; Toon Braeye; Izaak Van Evercooren; Christian Holm Hansen; Ida Rask Moustsen-Helms; Chiara Sacco; Massimo Fabiani; Jesús Castilla; Iván Martínez-Baz; Hinta Meijerink; et al. (Taylor & Francis Group, 2024)
Background We aimed to estimate XBB.1.5 vaccine effectiveness (VE) against COVID-19-related hospitalizations and deaths during BA.2.86/JN.1 predominance, among EU/EEA individuals with ≥65-years.Research design and methods We linked electronic health records to create historical cohorts in Belgium, Denmark, Italy, Navarre (Spain), Norway, Portugal and Sweden. We included individuals aged ≥65-years eligible for the autumnal 2023 COVID-19 vaccine. Follow-up started when ≥80% of country-specific sequenced viruses were BA.2.86/JN.1 (4/dec/23 to 08/jan/24) and ended 25 February 2024. At study site level, we estimated the vaccine confounder-adjusted hazard ratio (aHR) of COVID-19 hospitalizations and deaths between individuals with ≥14 days after vaccination versus unvaccinated in autumn 2023, overall, by time since vaccination and age groups. VE was estimated as (1-pooled aHR)x100 with a random-effects model.Results XBB.1.5 VE against COVID-19 hospitalizations was 50% (95%CI: 45 to 55) and 41% (95%CI: 35 to 46) in 65-79-year-olds and in ≥80-year-olds, respectively. VE against COVID19-related-death was 58% (95%CI: 42 to 69) and 48% (95%CI: 38 to 57), respectively, in both age groups. VE estimates against each outcome declined in all age groups over time.Conclusion Monovalent XBB.1.5 vaccine had a moderate protective effect against severe and fatal COVID-19 likely caused by BA.2.86/JN.1 during the 2023/2024 winter, among persons aged ≥65.